Usage of Saliva as Alternative Biological Fluid to Serum for Minerals, Energetic and Hormones Assessment in Lactating Egyptian Water Buffaloes - Hefnawy, Abdelghany; Shousha, Saad; Abdelhamid, Omnia; Youssef, Seham (Journal of Buffalo Science, 2013)
Blood sample is the most common biological fluid utilized for diagnosis and monitoring of diseases. Saliva contains locally produced substances as well as serum component, so the aim of this study is to compare the profile of minerals, energetic and hormones in Egyptian water buffaloes. Blood serum and saliva samples were collected from 80 healthy multiparous, non- pregnant lactating Egyptian water buffaloes. Both fluids were tested for sodium, potassium, chloride, calcium, phosphorous, magnesium, insulin, cortisol, ACTH, glucose, urea, creatinine, total protein and immunoglobulin [IgA]. The results revealed that, serum concentrations of calcium, glucose, total protein, sodium, chloride, Insulin, cortisol, ACTH and IgA were significantly higher than saliva. In contrast, the concentrations of potassium and phosphorous in the saliva were significantly higher than that of serum. On the other hand no significant change in respect of urea, creatinine and magnesium was noted between saliva and serum. The relationships between saliva and serum of the estimated parameters were significantly positive except the concentrations of insulin in saliva and blood serum did not correlate. In conclusion, the saliva sample can be used in clinical practice with high level of reliability and provide non-invasive biological fluid for monitoring of different parameters in Egyptian water buffaloes.